The impact of dengue viruses: Surveillance, response, and public health implications in Queensland, Australia - Alan Silburn; Joel Arndell (Elsevier, 2024)
This study examines dengue transmission, symptoms, vaccination efforts, treatment options, and global impact, focusing on Australia, especially Queensland. It evaluates current surveillance and response systems, identifies areas for improvement, and proposes strategies to enhance public health preparedness. Highlighting the socioeconomic impact of dengue outbreaks, the study underscores the need for integrated public health measures, effective vaccines, advanced surveillance methods, and sustainable mosquito control programs to mitigate the threat of dengue outbreaks and potential endemicity.